The Implementation of Memrise to Improve Speaking Ability on Secondary Level Students - Firdaus, Muhammad Ardan Firdaus; Jamilah, Jamilah (EDUPEDIA Publisher, 2024)
This research aims to analyze the development of students’ speaking skills in Vocational High School in Magelang, Central Java through classroom treatment by using CALL-Memrise. This classroom action research is implemented in a cyclical process, covering planning, acting, observing, and reflecting. The research subject was students in grade 11 in an EFL classroom, consisting of 34 students. The data were obtained from observation checklists, field notes, pretest, and post-tests. They were analyzed quantitatively by using SPSS. Quantitative data dealt with the teaching-learning process, i.e., students’ participation in classroom activities and assignments given to them. They were gained from pretest and post-test after treatment. The findings revealed that in cycle 1, the mean score was 1.84/4.00, the median score was 1,80/4,00, and the mode of the score was 1,80/4,00. In cycle 2, it showed that the mean of the score was 3,39/4.00, the median of the score was 3,30/4,00 and the mode of the score was 3,30/4,00. It can be concluded that the treatment has proved to be helpful in developing students’ speaking skills and could help the student improve their speaking skills based on accuracy, fluency and grammar.